Complications and fitting challenges associated with scleral contact lenses: A review. Issue 2 (April 2016) - Walker, Maria K.; Bergmanson, Jan P.; Miller, William L.; Marsack, Jason D.; Johnson, Leah A.
Highlights: Review of complications and fit challenges associated with scleral contact lenses. There is a low incidence of threatening infectious events reported. Hypoxia effects and inflammatory reactions are typically controllable. Midday fog, conjunctival prolapse, and epithelial bogging are common complications. Abstract: Introduction: The modern scleral contact lens (ScCL) has evolved from the very first contact lens fitted 128 years ago. Originally manufactured in glass and oxygen impermeable plastics, these lenses are available today in high Dk gas permeable materials that allow permeation of oxygen, reducing many of the complications that were seen with older generation ScCL. However, as with any new contact lens modality, the modern ScCL brings with it a new set of complications and fitting limitations. Methods: Pubmed searches under different keywords were conducted. Results: Existing literature provides some reports of infection with the scleral devices, although these are often seen in severely compromised corneas, while hypoxic and inflammatory complications are rarely reported in the literature. Furthermore, the somewhat complex relationship of a scleral lens on the eye can create fitting and removal challenges. Anomalies such as conjunctival prolapse, epithelial bogging, midday fogging, and limbal bearing have been reported, and appear to be unique sequelae to scleral lens wear. Conclusion: Although this revolutionary technology broadens the scope in which practitioners can treat patients with irregular ocular surfaces, reports of these complications indicate that there is still a need for continued research to further enhance the clinical outcomes of this promising contact lens modality.